La Constitución de Cádiz y la participación política popular en la Nueva España, 1808-1821. Balance y nuevas perspectivas - Guarisco, Claudia (Revista Complutense de Historia de América, 2008)
The article is about the popular sectors of the Viceroyalty of New Spain and their behavior with respect to the establishment of the Municipalities, under the Constitutional Monarchy. It is a balance, where the main contributions on the topic are analyzed. It also contains a proposal about the paths that future researches could take. The argument is that the perspective that had been dominant in the studies of the phenomenon should be complemented by views oriented to give account of the Popular Political Culture in which the Spanish Liberalism would have nested.